Numerical investigation and experimental validation of an infrared measurement approach for surface heat flux distribution using a multi-color-reference. (March 2019) - Mao, Yu-Feng; Li, Yun-Ze; Wang, Ji-Xiang; Wang, Jing; Jiang, Lixiang
Highlights: Measuring heat flux distribution by infrared camera with a multi-color-reference. Multi-color-reference with multiple emissivity supplies reference info for measurement. This method can measure the emissivity and heat transfer coefficient concurrently. Combining the advantage of contact and non-contact measurement. The novel model has been analyzed and verified by simulation and experiment. Abstract: Accurate measurement of heat flux (HF) is significant in both industrial engineering and scientific research. It is acknowledged that the radiative HF can be easily determined by radiometers. In order to measure the conductive or convective HF distribution flowing across a surface, this paper presents a novel non-contact measuring method based on the infrared (IR) technique and inverse heat transfer method (IHTM). In addition, a specially designed multi-color-reference (MCR) which is composed of four sectors with four different known emissivity will be attached to the focused surface in the practical measurement. Therefore, different radiation signals among the four different sectors of MCR as well as the focused surface will be detected by an IR camera, through which a whole radiation temperature map can be obtained. Based on the differences in the radiation temperatures of the surface and MCR, the IHTM can be adopted to yield useful boundary conditions such as emissivity of the surface, convective heat transfer coefficient, and the critical HF distribution. The measuring method presented in this study combines the advantages of contact and non-contact measurement, which can accurately obtain the HF distribution under the difficult-contacted conditions such as the HF monitoring of a boiling furnace, HF estimating of the aerodynamic heating surface, etc. Numerical simulation and experimental verification were organized to justify the newly-developed measuring method. Relative error in the simulation is estimated to be less than 2%, and that in the experiment is calculated to be around 4.23%. The result displays a relatively high precision of the measuring method, demonstrating that such a method can be applied in practical application.